An Assessment of the Value of Donor-derived Cell-free DNA Surveillance in Patients With Preserved Kidney Allograft Function. Issue 1 (1st August 2022) - Huang, Edmund; Haas, Mark; Gillespie, Matt; Sethi, Supreet; Peng, Alice; Najjar, Reiad; Vo, Ashley; Jordan, Stanley C.
Abstract : Background: Donor-derived cell-free DNA (dd-cfDNA) is a biomarker validated to detect rejection when measured to assess kidney allograft dysfunction. However, it remains unclear whether routine surveillance with dd-cfDNA provides additional information over standard monitoring of kidney allografts with creatinine and donor-specific antibodies (DSAs), particularly among those with little suspicion of rejection or injury. We investigated the value of measuring dd-cfDNA in patients with preserved allograft function and describe its association with future events. Methods: Three-hundred seventeen kidney transplant recipients with a creatinine ≤1.5 mg/dL, no current DSA, and no prior rejection were assessed with dd-cfDNA and categorized into low (dd-cfDNA <0.5%; n = 239), moderate (dd-cfDNA 0.5% to <1.0%; n = 43), and high (dd-cfDNA ≥1.0%; n = 35) groups. The occurrence of rejection, DSA, graft loss, and change in estimated glomerular filtration rate over time after dd-cfDNA assessment was compared. Results: Over follow-up, rejections were more commonly found among patients with high vs low dd-cfDNA (17% versus 5%; P = 0.01); a similar nonsignificant trend was observed among patients with moderate compared to low dd-cfDNA (12% versus 5%; P = 0.13). DSA development was uncommon and not different between groups (low: 4%; moderate: 3%; high: 0%; P = 0.52). There was only 1 graft loss in a patient with low dd-cfDNA, and dd-cfDNA was not associated with graft dysfunction over time. Conclusions: Most patients with elevated dd-cfDNA in conjunction with preserved allograft function remained stable over follow-up without deterioration in function or graft loss. Studies are needed to differentiate patients with elevated dd-cfDNA who will develop adverse outcomes from those who will remain clinically stable.